Evaluation of adherence to treatment by patients seen in a psychosocial care center in northeastern Brazil - Thaís Teles Souza; Wellington Barros Silva; Alexandre Sherlley Casimiro Onofre; Jullyana de Souza Siqueira Quintans; Fabiana Botelho de Miranda Onofre; Lucindo José Quintans-Júnior (Universidade de São Paulo, 2011)
In the treatment of mental disorders, nonadherence to medication, the main cause of psychiatric morbidity, is observed in about 50% of the cases and is responsible for numerous losses. This study evaluated adherence to drug treatment by patients seen in a Psychosocial Care Center (CAPS) in northeastern Brazil. Adherence to treatment was evaluated using the Haynes-Sackett and Morisky-Green-Levine tests. All patients registered in the CAPS were included in the study (n= 101). Only 11.88% of the patients adhered to drug treatment. The main reasons not to use medication were: oblivion (68.83%), feeling unwell after taking the medication (54.22%), not having money to buy the medication (43.83%), not finding the medication in the public health service (39.94%) and fear of harm that might be caused by the drug (28.90%). Furthermore, 85.1% of the patients did not know their diseases, 88.1% did not know their treatment, 86.4% did not feel good when they took their medication, and 88.1% took their medication incorrectly. The results revealed that the lack of information about diseases and drugs used, the nuisance posed by drug therapy and the low access to medications reduce adherence to treatment and, consequently, treatment effectiveness. No tratamento de desordens mentais, a não-adesão ao tratamento ocorre em cerca de 50% dos casos e é responsável por inúmeros prejuízos, além de ser a principal causa de morbidade psiquiátrica. O presente estudo objetivou avaliar a adesão ao tratamento medicamentoso de pacientes atendidos em um Centro de Atenção Psicossocial (CAPS) no Nordeste do Brasil. A avaliação da adesão ao tratamento foi feita através dos testes de Haynes-Sackett e Morisky-Green-Levine. Todos os pacientes cadastrados no CAPS foram incluídos no estudo (n = 101). Observou-se que apenas 11,88% dos pacientes aderiram ao tratamento medicamentoso. As principais razões para o não uso dos medicamentos foram: esquecimento (68,83%), sentir-se mal após a ingestão de medicamentos (54,22%), não ter dinheiro para comprar medicamentos (43,83%), não encontrar os medicamentos no serviço público de saúde (39,94%) e medo dos danos causados pelos medicamentos (28,90%). Além disso, observou-se que 85,1% dos pacientes não conheciam suas doenças, 88,1% não conheciam seus tratamentos, 86,4% não se sentiam bem quando usavam medicamentos e 88,1% usavam os medicamentos incorretamente. Os resultados demonstram que a falta de informação sobre doenças e medicamentos, os danos decorrentes da terapia medicamentosa e o baixo acesso aos medicamentos comprometem a adesão ao tratamento e, consequentemente, a eficácia do tratamento.